1981
DOI: 10.1172/jci110215
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the respiratory responses to external resistive loading and bronchoconstriction.

Abstract: A B S T R A C T The effects of resistive loads applied at the mouth were compared to the effects of bronchospasm on ventilation, respiratory muscle force (occlusion pressure), and respiratory sensations in 6 normal and 11 asthmatic subjects breathing 100% 02. External resistive loads ranging from 0.65 to 13.33 cm H20/liter per s were applied during both inspiration and expiration. Bronchospasm was induced by inhalation of aerosolized methacholine. Bronchospasm increased ventilation, inspiratory airflow, respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
0
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 30 publications
6
35
0
1
Order By: Relevance
“…The results of this study suggest that changes in respiratory drive are major determinants of the intensity of the sensation of dyspnoea experienced during progressive bronchoconstriction in asthmatic subjects. Our findings are in agreement with previous observations by KELSEN and co-workers [17]. These authors observed that both P0.1 and the sensation of breathing effort increased to a greater extent during MCh-induced bronchoconstriction than during breathing against an external resistance, thus indicating that the sense of breathing effort is related to the intensity of the respiratory drive rather than to the resistive load applied to respiratory system.…”
Section: A) B)supporting
confidence: 93%
See 2 more Smart Citations
“…The results of this study suggest that changes in respiratory drive are major determinants of the intensity of the sensation of dyspnoea experienced during progressive bronchoconstriction in asthmatic subjects. Our findings are in agreement with previous observations by KELSEN and co-workers [17]. These authors observed that both P0.1 and the sensation of breathing effort increased to a greater extent during MCh-induced bronchoconstriction than during breathing against an external resistance, thus indicating that the sense of breathing effort is related to the intensity of the respiratory drive rather than to the resistive load applied to respiratory system.…”
Section: A) B)supporting
confidence: 93%
“…The increase in P0.1 observed in the present study during MCh-induced bronchoconstriction was similar to that previously reported by others [6,16], and by ourselves [7]. The increase in respiratory drive during bronchoconstriction has been suggested to be due to the activation of reflexes arising from muscular and joint receptors stimulated by hyperinflation [16,17], and from airway receptors stimulated by inhaled substances and by bronchoconstriction [18][19][20]. The results of this study suggest that changes in respiratory drive are major determinants of the intensity of the sensation of dyspnoea experienced during progressive bronchoconstriction in asthmatic subjects.…”
Section: A) B)supporting
confidence: 92%
See 1 more Smart Citation
“…However, despite a close linear relationship between the decrease in FEV 1 and the increase in the POD, there is a considerable variation in the severity of breathlessness for any particular degree of airflow obstruction (1). Measuring the POD during external mechanical loading (resistive, elastic or threshold) less accurately simulates the mechanical characteristics of an asthma attack (20). However, it was previously shown that the imposed inspiratory threshold load is a good predictor for explaining the variability of the perceived dyspnea (21).…”
Section: Discussionmentioning
confidence: 98%
“…Inspiratory muscle training was associated with decreased dyspnea in patients with COPD and pretraining respiratory muscle weakness (19), and in patients with mild asthma and high beta 2 -agonist consumption but normal respiratory muscle strength (12). Inspiratory muscle training was evaluated in patients with various other respiratory disorders such as neuromuscular disorders (20) and cystic fibrosis (21), and in elite athletes (22), with favourable results.…”
Section: Discussionmentioning
confidence: 99%